Integrative Curriculum Management Model: The relation of Symbiosis-Mutualism Academic Subject Curriculum and Social Reconstruction in Modern Islamic boarding school of Darussalam Gontor Ponorogo - Abu Darda (Educan : Jurnal Pendidikan Islam, 2018)
Structure of the KMI (Kulliyyatul Muallallin al-Islamiyyah) curriculum includes the Islamic studies subjects group, Arabic studies subjects group, and the general sciences subjects group. KMI's curriculum tends to the model of subject academic and technologic curriculum.Guidance and Counseling for Santri who are responsible for non-formal education, its curriculum structure relates to the self expression or self-actualization for the development of life skills, both soft skills and hard skills. The Guidance and Counseling for Santri’s curriculum tends to the humanistic and social reconstruction curriculum model.The integrated management of the curriculum in Pondok Modern Darussalam Gontor is to conserve an equal balance of general education and religious education, active Arabic and English learning methods, and a disciplined boarding system; by using a holistic knowledge paradigm. All managerial functions of the KMI curriculum and Guidance and Counseling for Santri’s curriculum are intended to design the graduate as an ‘ulama and intellectuals, as the glue of ummah; as the intellectuals-‘ulama, not intellectuals who knows a little thing of religion; all graduate’s competencies are reflected in the mottoes: the noble character, sound body, broad knowledge, and independent mind.Management of curriculum integration of KMI and Guidance and Counseling for Santri design a beautiful configuration and symbiotic mutualism in reaching the goals of Pondok Modern Darussalam Gontor.